Hyperamylasemia as an early predictor of mortality in patients with acute paraquat poisoning. Issue 3 (March 2020) - Huang, Changbao; Bai, Lina; Xue, Xiang; Peng, Liangfei; Jiang, Jinghan; Zhang, Xigang
Objective: This study aimed to evaluate the relationship between elevated serum amylase levels and the prognosis of paraquat poisoning. Methods: Patients were categorized into the elevated and non-elevated serum amylase groups according to serum amylase levels. Demographics, mortality, risk factors of elevated serum amylase levels, and injury to the pancreas were analyzed. Results: A total of 457 patients were enrolled in this study and the overall mortality rate was 51.9%. Patients in the elevated group had worse indices than those in the non-elevated group. Kaplan–Meier survival analysis showed that the mortality rate in the elevated group was significantly higher than that in the non-elevated group (hazard ratio: 10.65, 95% confidence interval [CI]: 7.55–15.02). Multivariate Cox proportional hazards analysis showed that elevated serum amylase levels were related to mortality (hazard ratio: 2.066, 95% CI: 1.239–3.444). The receiver operating characteristic curve showed that the area under the curve was 0.724 (95% CI: 0.666–0.783) for serum amylase levels with 70.4% sensitivity and 74.0% specificity. Conclusion: Elevated serum amylase levels are observed in PQ poisoning. This elevation might be one of the most accurate early prognostic factors for predicting severity and mortality.